Influência da atividade minerária de fosfato na qualidade da água: caso do Rio Bezerra em Arraias-TO - Silva, Emanoel Santos da (Universidade Federal do Tocantins, 2022)
The present study aims to evaluate the water quality of the Bezerra River, municipality of Arraias/TO, considering the influence of the mining activity of phosphate exploration in relation to the springs inserted in the area object of study. Therefore, this work promoted a consolidation of data through the application of statistical methods, principal components analysis (PCA) and analysis of variance (ANOVA), for the treatment of historical monitoring results covering the Bezerra river basin, as well as the auxiliary application of water quality indicators. Through PCA, the first 4 principal components represented just over 70% of the total variance of the data. By ANOVA, it was indicated that at least one of the interactions between the groups analyzed in promoted spatial and temporal scale had a significant difference. Significant differences were also observed between the sampling campaigns conducted before and after the operational start of the mining enterprise in the study area. The indices applied in the analysis indicated, in general, intermediate trophic conditions in most of the sampled points and still satisfactory conditions for the water quality of the springs, despite relevant observations detected in relation to some of the parameters analyzed for the environment, with emphasis on the Total Phosphorus concentrations detected in the Bezerra River. It is concluded from the study carried out that there was significant interference of the enterprise on the quality of the water in the region, however, the monitored water resources are still in acceptable conditions regarding the quality of their waters.